Finite Control Set Model Predictive Control for Polysolenoid Linear Motor - Nguyen Hong Quang, Nguyen Phung Quang, Dang Danh Hoang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, the discontinuity of the voltage source inverter is considered when controlling Polysolenoid motors using model predictive control. When considering the instantaneous voltage across the motor with a non-ideal converter, the set of control voltages is finite and depends on the converter configuration. This is based on the finite control set model predictive controller (FCS MPC). When a finite set of voltage vectors is determined for the stator, the control signal processing capability of the system is significantly improved. Simulations are performed to illustrate the responsiveness of the force loop using the FCS-MPC method.